La sonorisation télévisuelle : mutations d’un marché dérivé et multiplication des formes de valorisation marchande des musiques de télévision - Guylaine GUÉRAUD-PINET (Tic & Société)
Since the 2000s, various sectors of the cultural industries have been undergoing profound changes, from the way they are organized to the way they edit content. Through an analysis of TV music editing, a sub-sector of the recorded music market, this article delves into the various strategies developed by actors in the phonographic and audiovisual sectors (especially those involved in the production of non-fiction TV programs such as magazines, newscasts, reality shows, etc.). Using the example of stock music, this article will shed light on the horizontal integrative strategies employed by the music majors (music library buyouts) and explore the shift toward the autonomization of television in the production of the music content that supports its image flow. The role of digitalization in bringing about these changes over the past fifteen years guides our study.